(untitled) (Research, Society and Development, 2022)
Premenstrual Syndrome (PMS) is a disorder that affects women of childbearing age with controversy about risk and protection factors. It is defined by a set of physical, emotional and behavioral symptoms that influence behavior and food consumption. Food can help prevent and treat the main symptoms of PMS. Thus, the present study aimed to investigate food consumption and its relationship with the main symptoms of PMS, the main associated factors and the inflammatory potential of food consumption. This cross-sectional study included 207 women between 18 and 40 years old, who live in the Federal District (DF). An online questionnaire was applied on the context of nutritional status, life habits, menstrual characteristics and food consumption through the FFQ. The weekly consumption of functional foods was: fruits and vegetables was 40.8% and 49.2%, respectively; of whole grains was 20.4%; roots and tubers, 8.9%. The predominant nutritional status among the population was the eutrophic profile corresponding to 49.2% of the participants. The most prevalent symptoms were subjective feelings of lack of emotional control (anxiety/depression), 81.3%; water retention, 68.8%; breast pain/sensitivity, 67.2%; and change in appetite, 64.1%. Menstrual cramps were frequent in 70.8% of the participants. Possible changes in serotonin levels are influenced by the low consumption of food sources of tryptophan, magnesium, vitamin B6 and omega-3, and when associated with a sedentary lifestyle and an inflammatory dietary profile, they increase susceptibility to PMS symptoms and the diagnosis.